Marketing Communication Strategy @Jessiebeauty.id Via Tiktok - Arcelia, Radhissa Rifka; Santoso, Budi (Universitas Widya Mataram, 2026)
This study aims to examine the marketing communication strategies employed by the local cosmetic brand @jessiebeauty.id through the TikTok platform. In the digital era, social media has developed into an effective marketing tool, including in building brand image and influencing consumer purchasing interests. This study uses a descriptive qualitative approach with the theory of Integrated Marketing Communication (IMC), specifically the promotion mix approach, which includes advertising, sales promotion, public relations, personal selling, and direct marketing. Data were collected through in-depth interviews with TikTok users who are followers of the @jessiebeauty.id account. This research focuses on the communication efforts made by the brand to introduce products, build interaction with the audience, and shape consumer perceptions through content uploaded on TikTok. Keywords: Marketing Communication Strategy; TikTok; Promotion Mix; Brand Image; Purchase Interest